A study of the infestations occurring in Parechinus Angulosus - Lewis, Veronica N; Lewis, Veronica N (Department of Biological Sciences, 2017)
Data on the ciliate infestation of the alimentary tract of echinoids has been steadily growing. Work has been done on sea urchins from Bermuda, Tortugas, the east and west coasts of Japan, the coast of North Carolina; the coast of California, the Mediterranean Sea. and the North Sea. The present paper deals with the sea urchin Parechinus Angulosus, the only species of sea-urchin to be found along the southernmost parts of the coast of South Africa. Five species of ciliate have been found, of which three appear to be new species. All of these species belong to the order Holotrichida. Apart trom the ciliates found a red Rhabdocoele worm of the genus Syndesmus has been found. It lies in the perivisceral cavity attached to the outside of the intestine, and appears to be a new species. Many of the ciliates found in sea urchins are closely related to free-living species, and are fairly cosmopolitan in distribution. A careful consideration of taxonomic status and of geographical distribution should therefore result in considerable information regarding the origin of the endozoic habit.